Effects and response of the Cerrado ground-layer to frost along the canopy cover gradient - Pilon, Natashi A. Lima; Cava, Mário G. B. [UNESP]; Hoffmann, William A.; Abreu, Rodolfo C. R.; Rossatto, Davi R. [UNESP]; Durigan, Giselda (Springer Nature, 2022)
Frost effects on savanna plant communities have been considered as analogous to those from fire, both changing community structure and filtering species composition. However, while frost impacts have been well-studied for the woody component of savannas, it is still poorly explored for the ground-layer community. Here, we investigated effects of frost in the Cerrado along a gradient of tree cover, focusing on ground-layer plant species, near the southern limit of the Cerrado in Brazil. We aimed to elucidate if the pattern already described for the tree layer also extends to the ground layer in terms of mimicking the effects of fire on vegetation structure and composition. We assessed how damage severity differs across species and across the tree-cover gradient, and we examined the recovery process after frost in terms of richness and community structure along the canopy cover gradient. Frost caused immediate and widespread dieback of the perennial ground-layer, with greatest impact on community structure where tree cover was lowest. However, frost did not reduce the number of species, indicating community resilience to this natural disturbance. Although frost mimicked the effects of fire in some ways, in other ways it differed substantially from fire. Unlike fire, frost increases litter cover and decreases the proportion of bare soil, likely hindering crucial processes for recovery of plant populations, such as seed dispersal, seed germination and plant resprouting. This finding calls attention to the risk of misguided conclusions when the ground layer is neglected in ecological studies of tropical savannas and grasslands.
Keywords: Disturbance; Frost; Litter accumulation; Neotropical savanna; Resilience